Aerosolizable Lipid-Nanovesicles Encapsulating Voriconazole Effectively Permeate Pulmonary Barriers and Target Lung Cells - Kaur, Ranjot; Dennison, Sarah R; Rudramurthy, Shivaprakash M; Katare, O P; Sharma, Teenu; Singh, Bhupinder; Singh, Kamalinder K (Frontiers in Pharmacology, 2022)
The entire world has recently been witnessing an unprecedented upsurge in microbial lung infections. The major challenge encountered in treating them is to ensure the optimum drug availability at the infected site. Aerosolization of antimicrobials, in this regard, have shown immense potential, owing to their localized and targeted effect. Efforts, therefore, have been undertaken to systematically develop lung-phosphatidylcholine based-lipid nanovesicles (LNVs) of voriconazole for the potential management of superinfections, like aspergillosis. LNVs, prepared by thin-film hydration method, exhibited a globule size of 145.4 ± 19.5 nm, PDI of 0.154 ± 0.104 and entrapment efficiency of 71.4 ± 2.2%, along with improved in vitro antifungal activity. Aerodynamic studies revealed microdroplet size of ≤ 5 µm, thereby declaring its potential to target the physical barrier of lungs effectively. The surface-active potential of LNVs demonstrated through Langmuir-Blodgett troughs indicated their ability to overcome the biochemical pulmonary surfactant monolayer barrier, while the safety and uptake studies on airway-epithelial cells signified their immense potential to permeate the cellular barrier of lungs. Pharmacokinetic studies showed marked improvement in retention profile of voriconazole in lungs following LNVs nebulization as compared to pristine voriconazole. Overall, LNVs proved to be safe and effective delivery systems, thus delineating their distinct potential to efficiently target the respiratory fungal infections.